The oncometabolite L-2-hydroxyglutarate is a common product of dipteran larval development. (December 2020) - Mahmoudzadeh, Nader H.; Fitt, Alexander J.; Schwab, Daniel B.; Martenis, William E.; Nease, Lauren M.; Owings, Charity G.; Brinkley, Garrett J.; Li, Hongde; Karty, Jonathan A.; Sudarshan, Sunil; Hardy, Richard W.; Moczek, Armin P.; et al.
Abstract: The oncometabolite L-2-hydroxyglutarate (L-2HG) is considered an abnormal product of central carbon metabolism that is capable of disrupting chromatin architecture, mitochondrial metabolism, and cellular differentiation. Under most circumstances, mammalian tissues readily dispose of this compound, as aberrant L-2HG accumulation induces neurometabolic disorders and promotes renal cell carcinomas. Intriguingly, Drosophila melanogaster larvae were recently found to accumulate high L-2HG levels under normal growth conditions, raising the possibility that L-2HG plays a unique role in insect metabolism. Here we explore this hypothesis by analyzing L-2HG levels in 18 insect species. While L-2HG was present at low-to-moderate levels in most of these species (<100 pmol/mg; comparable to mouse liver), dipteran larvae exhibited a tendency to accumulate high L-2HG concentrations (>100 pmol/mg), with the mosquito Aedes aegypti, the blow fly Phormia regina, and three representative Drosophila species harboring concentrations that exceed 1 nmol/mg – levels comparable to those measured in mutant mice that are unable to degrade L-2HG. Overall, our findings suggest that one of the largest groups of animals on earth commonly generate high concentrations of an oncometabolite during juvenile growth, hint at a role for L-2HG in the evolution of dipteran development, and raise the possibility that L-2HG metabolism could be targeted to restrict the growth of key disease vectors and agricultural pests. Graphical abstract: Image 1